Conformity and conflict readings in cultural anthropology - Spradley, James P.; McCurdy, David W. (Pearson Education, Inc., 2012)
This volume is an anthology of articles that cover a broad range of theoretical perspectives and demonstrate basic anthropological concepts. It incorporates successful articles from past editions and fresh ideas from the field to show fascinating perspectives on the human experience. The authors have added additional selections on globalization, medical anthropology, and applied anthropology.